Probing yields and angular distributions of Be(d,n) neutrons with novel target of compressed beryllium-powder; Radiation Physics and Chemistry; Vol. 197 - Shehada A. Abdullah; Krivobokov V. P. Valery Pavlovich; Lomov I. V. Ivan Viktorovich; Garapatski A. A. Alexander Alexandrovich; Mardelli R. Reema; Othman A. J. Ali (2022, 2022)
Title screen